Development of Civic Education Campus-Based at Muhammadiyah Universities in Central Java, Indonesia - Taniredja, Tukiran; Harmianto, Sri; Priyanto, Eko (EDUCARE, 2010)
ABSTRACT: The aims of main research are: (1) implementing the learning of civic education in democratic colleges; (2) the implementation of civic education campus-based embryo; and (3) implementing embryo of colleges as the laboratory of democracy. Research populations are all civic education lecturers and students of Muhammadiyah universities in Central Java who lecture and study civic education. Research methods are: interview, scale of attitude/opinion, questionnaire, and documentary study. Data of research are described with data reduction technique, data display, and conclusion. Conclusions are: (1) to create democratic civic education learning, student discussions should be stepped up to develop studentsâ civic values; and (2) to create embryo of civic education campus-based and embryo of college as the laboratory democracy. It needs: (a) efforts to create democratic college both in its intra-curriculum and extra curriculum; (b) implementing student-oriented lectures; (c) students are involved to participate in any political state activities; (d) making of student study groups; (e) implementing the freedom of having a notion, gender equality, and responsibility; (f) increasing number of studentsâ discussion about reality of social life, and its problem solving; (g) increasing number of studentsâ academic groups, and training them to obey in any rules; (h) in implementing the three college-dedications, lecturers have to involve their students; (i) college has to give students more chances to develop their potential; and (j) students should be introduced with democratic values earlier. Â KEY WORDS: civic education, campus based education, Muhammadiyah universities, laboratory of democracy, and democratic civic education.Â Â About the Authors: Prof. Dr. Haji Tukiran Taniredja is Senior Lecturer at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh PO Box 202, Purwokerto 53182, Central Java, Indonesia; and Sri Harmianto and Eko Priyanto are also Lecturers at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto). They can be reached at: tukiranump@yahoo.com and info@ump.ac.idHow to cite this article? Taniredja, Tukiran, Sri Harmianto & Eko Priyanto. (2010). âDevelopment of Civic Education Campus-Based at Muhammadiyah Universities in Central Java, Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.2(2) February, pp.153-170. . Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 27, 2009); Revised (January 15, 2010); and Published (February 17, 2010).